2011
DOI: 10.1007/978-3-642-19260-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Operating a Network Link at 100%

Abstract: Abstract. Internet speed at the edge is increasing fast with the spread of fiberbased broadband technology. The appearance of bandwidth-consuming applications, such as peer-to-peer file sharing and video streaming, has made traffic growth a serious concern like never before. Network operators fear congestion at their links and try to keep them underutilized while no concrete report exists about performance degradation at highly utilized links until today. In this paper, we reveal the degree of performance degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…With simultaneous Eqs. (5) and (6) mentioned in Sect. 4.2, we can quantitatively calculate the above ratios for all traffic types and calculate the difference among the traffic types.…”
Section: Equilibrium For Heterogeneous Trafficmentioning
confidence: 94%
See 3 more Smart Citations
“…With simultaneous Eqs. (5) and (6) mentioned in Sect. 4.2, we can quantitatively calculate the above ratios for all traffic types and calculate the difference among the traffic types.…”
Section: Equilibrium For Heterogeneous Trafficmentioning
confidence: 94%
“…By solving Eqs. (5) and (6), we can obtain the solution of L t and actualized traffic T t given D t . This solution is actualized as an equilibrium of the closed-loop of traffic increase → QoS degradation → traffic reduction.…”
Section: Derivation Of Packet-loss Ratio and Actualized Traffic As Eqmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analysis such as auto/cross-correlation among traffic and QoS time series have also been investigated [11]. Several measurement results on overloaded links have been published [3], [12], [13]. For example, Luckie et al investigated RTT (round-trip time) and packet loss time series of an inter-AS link and found that the diurnal pattern of RTT and packet loss increases to about a 70 ms delay and a 2 ∼ 3% packet loss ratio [3].…”
Section: Related Workmentioning
confidence: 99%